STUDY THE INFLUENCE OF WATER QUALITY ON FILTER PERFORMANCE WITH DIFFERENT FLOW RATE AND CONTAMINANT CONCENTRATIONS - P.A. Gawande,; P.G Bhambarkar,; A.N. Mankar, (International Journal of Innovations in Engineering Research and Technology, 2014)
The high initial cost of drip irrigation system is considered to be its limitation for large scale adoption. Due to high initial cost, the marginal land holders are not in a position to install drip irrigation system and thus will not in a position to increase the crop production. Out of all components, filter unit is the most expensive component. But it is essential, without filter unit, drip system will not run efficiently. This study will enable to select the proper type of filter required by the farmer depending upon the water quality. The filtration efficiency was determined for the known concentration of impurities i.e. 100, 200, 300 and 400 ppm for sand, screen and disc filter at three constant flow rates viz. 1.5 lps, 2 lps and 2.5 lps. The pressure drop characteristics were monitored at inlet and outlet of the filters. The result of experiment depicts that the filtration efficiency decreased with increase in levels of concentrations of impurities. The efficiency of the disc filter was found maximum, followed by the screen and sand filter. The pressure drop across the filter increased with different levels of concentration of impurities with elapsed time and flow rates. It was found that the time required to develop 5 m of pressure drop across the disc filter was minimum, followed by the screen and sand filter.